Tradisi Jimpitan sebagai Resepsi Sosial Al-Qur'an: Studi Living Qur'an pada Masyarakat Desa Ganting Kabupaten Sidoarjo - A. Amir Firmansyah; Ahidul Asror (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
The jimpitan tradition, a community-based mutual assistance practice, continues to endure amid modernization. However, studies examining this tradition through the Living Qur’an perspective remain limited. Previous research has predominantly focused on its social, economic, and community empowerment dimensions, while the processes through which Qur’anic values are internalized, practiced, and transmitted have received little attention. This study aims to analyze the manifestation of Qur’anic values within the jimpitan tradition in Ganting Village, Gedangan District, Sidoarjo Regency, and to explain how Qur’anic teachings are internalized in community social practices. This study employs a descriptive qualitative approach within the Living Qur’an framework. Data were collected through observation, in-depth interviews, documentation, and literature review, and analyzed using Miles and Huberman’s interactive model, supported by NVivo software for thematic mapping through tree-map visualization. The findings reveal that the jimpitan tradition is routinely practiced through nightly collections of rice or monetary contributions, which are collectively managed for social and communal purposes. From the Living Qur’an perspective, this practice embodies the values of ta‘āwun (mutual assistance), ukhuwah (brotherhood), generosity, sincerity, social responsibility, and concern for vulnerable groups. These values correspond closely with Qur’anic teachings, particularly Q.S. Al-Mā’idah [5]:2, Q.S. Al-Hujurāt [49]:10, and Q.S. Al-Mā‘ūn [107]:1–3. The study’s novelty lies in interpreting jimpitan as a form of social reception of the Qur’an, demonstrating that Qur’anic teachings are not merely understood textually but are also embodied in local cultural practices. Theoretically, this study contributes to Living Qur’an scholarship by highlighting local traditions as effective media for transmitting and actualizing Qur’anic values in social life.